(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Biocatalysis is attracting increasing attention in order to obtain low molecular weight substances - reagents for directed synthesis [1]. It is known that the type of plant material and the method of separating cellulose from it determine the physicochemical properties of the substrate, therefore, determine the reactivity to enzymatic hydrolysis [2-4]. That is why the dependence of the fermentolysis of cellulose substrates on the characteristics of cellulose (degree of grinding, crystallinity, polymerization, the presence of non-cellulosic impurities, etc.) is the subject of many studies [3, 5,].